A Chinese version of the young children's participation and environment measure: psychometric evaluation in a Hong Kong sample. Issue 21 (9th October 2021) - Chien, Chi-Wen; Leung, Cynthia; Schoeb, Veronika; Au, Alma
Abstract: Purpose: To investigate the psychometric properties of a Chinese-translated version of the Young Children's Participation and Environment Measure. Materials and methods: The Young Children's Participation and Environment Measure was translated into Chinese using cultural adaptation by adding/replacing with activities relevant to Chinese culture. Parents of 53 children aged 2–5 years with developmental disabilities and of 50 typical developing children completed the questionnaires. Internal consistency, test–retest reliability, known-group validity, and discriminant validity were examined using Cronbach's alpha, intraclass correlation coefficient, Mann–Whitney U tests, and Spearman's rank correlation coefficients respectively. Results: Internal consistency was acceptable for most scales ( α = 0.42–0.89). Test–retest reliability of the summary scores was moderate to high for all scales (intraclass correlation coefficient = 0.65−0.90). Known-group validity was supported by demonstrating significant differences by disability status in all community participation scales, two daycare/preschool participation scales, and one home participation scale. Low or negative correlations between the scores of some scales and children's cognition ( ρ = 0.27–0.32; –0.36–to–0.35) and parental stress ( ρ = –0.42–to–0.31) supported discriminant validity. Conclusion: This study provided psychometric evidence supporting the use of the Young Children's Participation and Environment Measure to assess Chinese children's participation and environmental support. IMPLICATIONS FOR REHABILITATION: The Young Children's Participation and Environment Measure is translated into Chinese using a cultural adaptation process. The Chinese version of the Young Children's Participation and Environment Measure demonstrates evidence for internal consistency, test–retest reliability (including the minimal detectable change). The Chinese version of the Young Children's Participation and Environment Measure demonstrates evidence for known-group validity and discriminant validity. The Chinese version of the Young Children's Participation and Environment Measure holds promise for use in children aged 2−5 years to assess their participation and identify environmental barriers warranting intervention.